THE FIRST CAPYBARAS (RODENTIA, CAVIIDAE, HYDROCHOERINAE) INVOLVED IN THE GREAT AMERICAN BIOTIC INTERCHANGE (Ameghiniana, 2015)
The new combination Phugatherium dichroplax nov. comb. (Ahearn and Lance) is proposed for the North American species “Neochoerus” dichroplax Ahearn and Lance, and “N.” cordobai Carranza-Castañeda and Miller. Its age range is here expanded (late Early Blancan–latest Blancan; Piacenzian–Gelasian), being the youngest species of Phugatherium and thus extending the biochron of the genus into the early Pleistocene. This is the first mention of a Pliocene South American lineage of capybaras crossing the Panamanian bridge, implying the recognition of a third lineage of capybaras involved in the Great American Biotic Interchange. The proposed North American origin of the genus Neochoerus is discussed.Resumen. LOS CARPINCHOS (RODENTIA, CAVIIDAE, HYDROCHOERINAE) Y EL GRAN INTERCAMBIO BIÓTICO AMERICANO. Se propone la nueva combinación Phugatherium dichroplax nov. comb. (Ahearn y Lance) para las especies “Neochoerus” dichroplax Ahearn y Lance y “N.” cordobai Carranza-Castañeda y Miller de América del Norte. Esta es la especie más joven del género. En este trabajo se extiende el biocrón de la especie (Blanquense Temprano tardío a Blanquense Tardío; Piacenciano–Gelasiano) así como el del género hasta el Pleistoceno Temprano. Esta es la primera mención de un linaje de carpinchos pliocénicos sudamericanos que atraviesan el puente de Panamá, implicando el reconocimiento de un tercer linaje de carpinchos involucrado en el Gran Intercambio Biótico Americano. Se discute el origen norteamericano del género Neochoerus.